Answer:
The slope of the tangent m = -0.0833
Step-by-step explanation:
<u><em>Step(i):-</em></u>
Given that the curve
x y - 2y² + x² = -5 ...(i)
Differentiating equation (i) with respective to 'x', we get
![x(\frac{dy}{dx} )+y (1) -2(2y)\frac{dy}{dx} + 2x=0](https://tex.z-dn.net/?f=x%28%5Cfrac%7Bdy%7D%7Bdx%7D%20%29%2By%20%281%29%20-2%282y%29%5Cfrac%7Bdy%7D%7Bdx%7D%20%2B%202x%3D0)
![x(\frac{dy}{dx} ) -2(2y)\frac{dy}{dx} = -2x-y](https://tex.z-dn.net/?f=x%28%5Cfrac%7Bdy%7D%7Bdx%7D%20%29%20-2%282y%29%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20-2x-y)
![(x -4y)\frac{dy}{dx} = -2x-y](https://tex.z-dn.net/?f=%28x%20-4y%29%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20-2x-y)
![\frac{dy}{dx} = \frac{-2x-y}{x-4y}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20%5Cfrac%7B-2x-y%7D%7Bx-4y%7D)
<u><em>Step(ii):-</em></u>
<u><em>The slope of the tangent</em></u>
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
m = ![\frac{-2+1.5}{1+6}](https://tex.z-dn.net/?f=%5Cfrac%7B-2%2B1.5%7D%7B1%2B6%7D)
![m = \frac{-0.5}{6} = -0.083](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B-0.5%7D%7B6%7D%20%3D%20-0.083)
The slope of the tangent m = -0.0833
<u><em></em></u>
<u><em></em></u>